Changing dogma regarding the conformation of electron transferring menaquinone (MK) - Magallanes, Estela Serrano, author; Crans, Debbie C., advisor; Menoni, Carmen S., committee member; Tsunoda, Susan, committee member (Colorado State University. Libraries, 2017)
Menaquinone-9 (MK-9) is the natural substrate containing a naphthoquinone and an isoprenyl side-chain with nine isoprene units that carry out the electron transfer for the Mycobacterium tuberculosis. We present studies aiming to understand the chemical and biochemical properties of hydrophobic MK molecules. Specifically, we are investigating the MK derivative with two isoprene units, MK-2, because it provides us with the base structure containing the naphthoquinone unit and the isoprene side-chain. Its synthesis is relatively simple because the precursors are commercially available, which allows for large scale preparation and detailed characterization of the molecular structure under different conditions. Using 1D and 2D 1H NMR studies we are establishing that MKs have different conformations depending on the specific environmental conditions. Similarly, we show using 1H-1H 2D NOESY NMR studies that the association of MK with the surfactant- water interface of reverse micelles, which is a model membrane system, modify the conformation of the menaquinone derivative. Finally, the redox potentials of MK-2 was measured in the three different solvents (DMSO, CH3CN and pyridine). We hypothesize that the redox potential is correlated to the conformational of the MK. We observed that the redox potentials varied with solvent. The observed folded structures of MK derivatives stand in contrast to the linear conformation shown in life science text books.
Keywords: menaquinone; characterization; Mycobacterium tuberculosis